Tribological properties of graphene oxide as a lubricating additive in water and lubricating oils - Hiroshi KINOSHITA (The Japan Society of Mechanical Engineers, 2015)
High-performance lubricating additives are desired in order to improve the properties of lubricating fluids. Recently, carbon nanomaterials such as fullerenes, carbon nanotubes, and carbon onions have been studied as lubricating additives for water and lubricating oils. However, the costs of these carbon nanomaterials are too high for practical use. On the other hand, graphene oxide (GO) is a carbon nanomaterial that consists of single atom thick sheets that possess a large number of oxygen functional groups. Since GO is synthesized from graphite using a chemical liquid process, the cost of GO is significantly lower than other carbon nanomaterials. In this study, the application and tribological properties of GO monolayer sheets as additives in water and poly-alpha olefin (PAO) were investigated. The dependence of the friction coefficient of GO-water dispersions on GO concentration (0.01-1.0 mass %) was investigated. In particular, GO-water dispersions with a concentration of less than 0.1 mass % demonstrated low friction coefficients. In this study, GO was simply dispersed in PAO using surfactant and intermediary solvents without the need for drying treatments. We found that the use of anionic surfactants in the GO-PAO dispersions was better than cationic surfactants in terms of the degree of wear observed. Specifically, GO-PAO dispersions that used an anionic surfactant with a GO concentration of 4 mass % had the smallest wear in this study. Moreover, friction coefficients were not decreased by the addition of GO in PAO. Finally, we found that intermediary solvents did not affect lubrication.